Barn och ungdomars upplevelse av utsatthet - Jatko, Evelina (2011)
The purpose of this thesis was to examine, and describe, children´s and young people's perception and experience of vulnerability. Through a questionnaire study answers to the questions: What is vulnerability according to children and adolescents? What are the experiences children and adolescents have of vulnerability? What can be done to prevent exposure? were sought. The study was initiated by the Red Cross, which was interested in the concept of vulnerability according to children in grades six to nine in the city of Luleå. Through this, the Red Cross would be able to put collected money where they are most needed. Previous research has shown the number and severity of consequences of vulnerability and emphasizes the role of the school and the family in protecting children and young people from being put in vulnerable situations. The theoretical background of the thesis includes theories about children's needs and definitions of vulnerability. The results showed that many students in the selected grade levels feel, and have felt, vulnerable and that they perceive vulnerability as everything from bullying to unfavorable conditions at home. Students proposed that courses and lectures in vulnerability and its consequences should be held in schools for prevention against this. Validerat; 20111107 (anonymous)